Pencegahan Stunting di Kabupaten Pasuruan dengan Pelatihan Pengolahan Ikan Gabus - Handayani, Handayani (Journal of Dedicators Community, 2022)
Stunting prevention in children under five is the main program of the Indonesian government. This community service aims to provide education about stunting and its prevention, the snakehead fish benefits and training on how to process it into products.Â  From Focus Group Discussion of the Medical faculty of Universitas Nahdlatul Ulama Surabaya Team with the chairman of Fatayat NU Bangil, known that members of Fatayat NU Bangil are not familiar with snakehead fish and how to process it, nor does anyone have an independent business of processed snakehead fish. The training was held on December 24, 2021 at the Anisah Foundation building, Bangil district in Pasuruan, attended by 50 participants. The presenter were from the Chairman of the PasuruanRegency Forikan, Department of Industry and Trade, the Pasuruan Regency Fisheries Service. The post test results showed that after the training the participants had understood about stunting and its prevention, snakehead fish benefits and could also process food made from snakehead fish. To encourage independent business partners, the Community Service Team also freezer, mixer impulse sealer. It is hoped that after this activity participants can socialize eating fish habit and can also produce processed food from snakehead fish.